Non-Adherence Factors Associated with the Use of Rivaroxaban Among Patients with Deep Venous Thromboembolism: A Single Center Observational Study - Shoaib Muhammad Badini, Zia Ur Rehman, Muhammad Ammar Pirzada, Shahid Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: To assess the rate and factors associated with non-adherence of Rivaroxaban in patients with deep venous thrombosis. Methodology: An observational longitudinal study was conducted at the Department of Surgery, Aga Khan University & Hospital, Karachi between June 2022 to November 2022. Patients with known malignancy with or without chemotherapy, those with a known diagnosis of hypercoagulability disorder or a history of limb trauma leading to deep venous thrombosis were included in the study. Patients who have refused to start rivaroxaban treatment prescribed by vascular surgeons, those with cognitive disabilities, such as dementia, who need to rely on a caregiver for their medical care were excluded. The frequency of missed doses, side effects, and causes of non-adherence to the prescribed treatment were recorded. Results: A total of 180 patients were recruited with a mean age of 66.3 ± 8.2 years. Out of 180 patients, 111 (61.6%) missed at least one dose during treatment. We reported the self-reported adherence of 70%. 72 (30%) were non-adherent. Majority revealed that they forget to take medicine; 78 (43.3%) or experienced side effects; 60 (33.3%). Five patients were hospitalized due to serious adverse events (bleeding per rectal and gastrointestinal). Conclusion: A significant percentage of non-adherence among participants was found in our study. One of the primary causes of non-adherence was forgetfulness. We recommended that patients get appropriate counseling on the expected results and negative effects of the medicine in order to promote adherence to Rivaroxaban. Keywords: Adherence, compliance, deep venous thrombosis, Rivaroxaban